(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article analyzes the socio-psychological problems of the re-socialization of internally displaced persons. Among the main problems of this category of residents of Ukraine is the problem of reducing social activity. The lack of social activity, in turn, complicates the processes of adaptation to a new place of residence and re-socialization. The psychological symptoms characteristic of migrants that make up "Migrant syndrome" are considered. "Migrant syndrome" consists of the following symptoms: rental units; the position of the "victim"; symptom evacuation; symptom of missed opportunities; symptom of exclusivity; a symptom of a lost future; a symptom of lost happiness, and also a symptom of learned helplessness. Rental installations of internally displaced persons depended on the constant humanitarian assistance of the Center and citizens. The position of the "victim" was that migrants considered themselves to be a victim of circumstances and did not consider themselves to be the subject of their life. The symptom of the evacuation was that the settlers considered the new place of residence temporary and did not try to change it according to their needs. The symptom of missed opportunities was due to the fact that the settlers left their housing, work, business and did not see an opportunity to materialize in a new place. The symptom of the exclusivity of migrants manifested itself in the fact that they did not accept their life difficulties and did not want to make efforts to overcome them, but only required external support. The symptom of a lost future was that this contingent believed that all achievements were in the past, and nothing was waiting for them ahead. The symptom of lost happiness is associated with previous symptoms and is that these people are sure that they will never be able to become happy because they have suffered irreparable losses. The symptom of learned helplessness among the immigrants was developed when they endlessly faced insurmountable obstacles and they had the impression that they could do nothing. Ways of overcoming the indicated syndrome and methods for the formation of social interest and social activity of immigrants by introducing them to volunteer activities, which, in turn, contribute to the process of re-socialization, are proposed. We have offered volunteer trainings on the basis of the Kiev Centre for Assistance to Refugees and Migrants. The training suggested the formation of ideas about the possibilities of volunteering and its role in the personal growth of a volunteer. The objectives of the trainings included: the development of social activity; development of skills in the field of volunteer management, as well as assistance in building life plans. The trainings contributed to the reorientation of migrants from the objects of volunteer assistance to the subjects. Presents the results of the overcoming the "Migrant Syndrome", which was achieved by volunteers. As shown by our research conducted at the Center, immigrants who are actively involved in volunteer’s work have largely lost the symptoms that make up the "Immigrant Syndrome". Active citizenship and social activity, which was formed in this category of persons was the key to their re-socialization and further personal growth.